The SHORT! guide to producing : the practical essentials of producing short films - Merzbacher, Charles (Routledge, Taylor & Francis Group, 2018)
"In this book, Charles Merzbacher offers a concise, definitive guide to the essential skills, techniques, and logistics of producing short films, focusing on the practical knowledge needed for line producing and overseeing smaller-scale productions. Merzbacher, a longtime instructor and accomplished filmmaker, takes producers through every stage of the production processfrom preproduction and planning to the producers role in postproduction and distributionweaving together best practices with insights from real-life production scenarios. Key topics include: Finding a worthy project Schedules and budgets Managing the casting process Recruiting and managing crew Location scouting Legal and safety issues Running a production Negotiating music rights And much more!An accompanying websiteavailable at theshortseries.comoffers document templates (for contracts, call sheets, budgets and other production paperwork), fully completed paperwork to use as samples, video interviews and more."--Provided by publisher.